Rubella virus and rheumatoid arthritis. Issue 1 (February 1977) - Hart, H; Marmion, B P
Abstract : A collection of synovial fibroblasts from 19 patients with rheumatoid arthritis (RA) and 12 patients with osteoarthrosis or other non-RA disease has been examined for rubella virus antigens by immunofluorescence and radioimmunoassay with negative results. Eluates of synovial membrane prepared under conditions likely to dissociate antigen-antibody complexes have shown no rubella antibody. A serological survey of RA patients and those with other forms of arthritis has shown no differences in the frequency or levels of rubella haemagglutination-inhibiting antibody. These results provide little support for various hypotheses that a persistent infection with rubella virus underlies or initiates the rheumatoid process.